2017
DOI: 10.3390/app7040322
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Supercritical Carbon Dioxide and Ethanol for the Extraction of Phenolic Compounds from Chokeberry Pomace

Abstract: Chokeberry (Aronia melanocarpa (Michx.) Elliot) is a fruit with exceptionally high levels of phenolic compounds which are accumulated mainly in the peel; hence, the majority remains in the leftovers after juice production. Extraction with the use of carbon dioxide in supercritical conditions was used to isolate phenolic compounds from the pomace. The effect of the process parameters (temperature; pressure; and the addition of ethanol) on the extraction yields and properties of the extracts was investigated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…As it is known, these compounds are polar, so a more polar solvent will extract them better. Other authors such as Woźniak et al [ 26 ], Chew et al [ 27 ] and Paini et al [ 28 ] also used mixtures with ethanol to improve the yield of polyphenols extraction. In the case of flavonoids, no statistically significant differences were found on the extraction yield of dihydroxybenzoic acids and flavones when varying these parameters.…”
Section: Resultsmentioning
confidence: 99%
“…As it is known, these compounds are polar, so a more polar solvent will extract them better. Other authors such as Woźniak et al [ 26 ], Chew et al [ 27 ] and Paini et al [ 28 ] also used mixtures with ethanol to improve the yield of polyphenols extraction. In the case of flavonoids, no statistically significant differences were found on the extraction yield of dihydroxybenzoic acids and flavones when varying these parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The pressure of 200 bar was required to obtain the satisfactory extraction efficiency. In a comparison with the studies performed by Li et al [ 147 ], Woźniak et al [ 109 ] performed the extraction with carbon dioxide and ethanol (20, 50, 80%, m / m ) as a modifier. The optimal conditions for the Chokeberry (Aronia melanocarpa) extraction were 35 °C, 100 bar and 80% ( m / m ) of ethanol.…”
Section: Separation Of Phenolic Compounds With Supercritical Co mentioning
confidence: 99%
“…Studies on the influence of temperature and pressure on the extraction process of bioactive substances gave different results due to the plant materials and targeted compounds [ 40 , 42 , 44 , 45 , 46 , 47 , 48 ]. For example, high pressures were reported to enhance the global extraction yield of phenolic compounds [ 40 , 45 , 47 ], while Akay et al [ 46 ] reported a high total phenolic content under low pressure and no significant difference to the yield when increasing temperature and pressure. Some results showed that an augmentation in the recovery of phenolic compounds could be obtained by reducing the extraction temperature and increasing the addition of co-solvent and pressure [ 45 ].…”
Section: Parameters To Consider and Their Effect During Supercritimentioning
confidence: 99%